Analysis of Difficulty Levels and Discriminating Power of Items Made by Junior High School Mathematics Teachers - Nasruddin Nasruddin; Herlina Herlina; Samsul Madil (Budapest International Research and Critics University, 2021)
This study aims to determine the quality of mathematics subject matter for class VIII SMP Negeri 12 Poleang Barat based on discriminatory power and level of difficulty. This research is categorized as descriptive research. Techniques used to collect data are interviews and documentation. The data analysis conducted in this study consisted of an analysis of the level of difficulty, and an analysis of discriminating power. Based on the results of research and discussion of item analysis which includes the level of difficulty and distinguishing power on the Final Even Semester Final Assessment Essay for Mathematics Subject Class VIII SMP Negeri 12 Poleang Barat for the 2020/2021 academic year. From the results obtained, it can be concluded that from a total of 5 essay questions in terms of the level of difficulty, it shows that the final assessment items for the even semester class VIII mathematics subjects have a level of difficulty which states that there are 2 items that are considered difficult (6%), questions that are difficult. including the medium category there are 2 questions (27%), and the questions that are included in the easy category have 1 question (43%). Meanwhile, in terms of discriminatory power, it states that as many as 2 questions (18%) have poor discriminatory power, 1 question (23%) has moderate discriminatory power, 1 question (54%) has very strong discriminating power.